Differential pulse anodic stripping voltammetry of cadmium, copper, lead and zinc in the presence of N,N’-bis[2-hydroxyacetophenone]ethylenediamine - Mohd. Yusof, Nur Yasarah (2014)
Voltammetry is a low cost and sensitive technique for the detection of heavy metal ions such as Cd(II), Cu(II), Pb(II) and Zn(II). However, the use of glassy carbon electrode as the working electrode suffers from surface fouling that renders poor detection performance towards these metal ions. In the present study, the potential of a Schiff base namely N,N’-bis[2-hydroxyacetophenone]ethylenediamine (OAcPh-en) to enhance the sensitivity of voltammetric technique using glassy carbon electrode for the detection of these metal ions were investigated. Complexation ability of OAcPh-en towards these metals was investigated using liquid-liquid extraction with chloroform followed by detection using inductively coupled plasma-mass spectrometry. In this study optimum parameters used for Cd(II) ions; pH 5.0, contact time 120 s, metal concentration 60 μg/mL and OAcPh-en concentration 0.2 M for the complexation of the metal-OAcPh-en was examined. In-situ approach was adopted throughout this study for the enhancement of metal ion detection by OAcPh-en using cyclic voltammetry and differential pulse anodic stripping voltammetry. Optimum experimental parameters for Cd(II) ions; pH 8.0, addition of acetonitrile 80 μL, OAcPh-en concentration 25×10-5 M, scan rate 10 mV/s, accumulation time 60 s and accumulation potential -0.9 V were obtained. OAcPh-en shows slightly better liquid-liquid extraction for Cd(II) (99.10%) than Cu(II) (89.94%), Pb(II) (78.03%) and Zn(II) (55.93%). The OAcPh-en shows irreversible oxidation peak around +1200 mV vs Ag/AgCl (3.0 M). The relationship between peak current and metals concentration was linear for Cd(II) and Cu(II) in acetonitrile in the range of 0.04-0.68 μg/mL and 0.01-0.24 μg/mL respectively. The detection limit is 0.065 ng/mL for Cd(II) and 0.002 ng/mL for Cu(II) respectively. The newly developed method was successfully applied in the determination of Cd(II) and Cu(II) in mineral water sample and natural tap water.